Spatial network configurations of cargo airlines - Aaron B. Scholz (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
The paper evaluates the spatial dimension of air cargo networks by means of concentration and centrality measures. Three groups of carriers are analyzed, namely combined carriers, their pure freighter operations and pure cargo airlines. Differences in their spatial network configuration are observed between the three groups. Combined carriers operate very centralized networks with high concentrations at a small number of airports. Hub-and-spoke schemes are their predominant network configuration. The freighter fleets of combined carriers have lower centrality and concentration scores but hub-and-spoke schemes are still the predominant network configuration. Pure cargo airlines operate the least concentrated and centralized networks. Round-trip configurations are wide spread among pure cargo airlines to cope with imbalances of demand.
urn:nbn:de:swb:90-227914
Keywords: 330; air cargo transport; network configuration; centrality; spatial network configuration